Hybrid Solder Joints: Viscosity Studies of the Nanocomposite Flux with Fe Nanoparticle Additions - Andriy Yakymovych; Irina Wodak; Golta Khatibi (Metals)
Viscosity is one of the most important physical characteristics of choosing a flux for solder paste. However, not in all cases do the producers give information about the viscosity of commercial flux. A recent promising trend is to mix various kinds of nanoparticles with solder paste or flux and investigate the produced solder joints. However, the impact of nanosized inclusions on the viscosity of the flux has practically not been investigated. In this study, the temperature and shear rate dependencies of the viscosity of the nanocomposite flux were measured. For this purpose, the commercial flux has been mixed with Fe nanoparticles up to 2.0 wt.% of inclusions. It has been shown that viscosity increases with the addition of Fe nanoparticles. However, it is valid only for first heating up to circa 340 K. The viscosity values of the flux with and without nanosized inclusions are practically similar by further heating to 360 K as well as by subsequent cooling. Additionally, the performed differential thermal analysis has shown the heat effects, which are in good agreement with viscosity behavior.